DNA sensing by field-effect transistors based on networks of carbon nanotubes - Rogers, John A. (2012)
We report on the sensing mechanism of electrical detection of deoxyribonucleic acid (DNA) hybridization for Au- and Cr-contacted field effect transistors based on single-walled carbon nanotube (SWCNT) networks. Barrier height extraction via low-temperature electrical measurement provides direct evidence for the notion that the energy level alignment between electrode and SWCNTs can be affected by DNA immobilization and hybridization. The study of location-selective capping using photoresist provides comprehensive evidence that the sensing of DNA is dominated by the change in metal−SWCNT junctions rather than the channel conductance.